PENGARUH SPESIALISASI AUDITOR DAN UKURAN K.A.P TERHADAP KUALITAS AUDIT DENGAN KOMITE AUDIT SEBAGAI VARIABEL PEMODERASI - Moh. Tahang; Haris Sarwoko; Siti Asmanah (JURNAL LENTERA BISNIS, 2024)
Audits can mitigate the opportunistic actions of agents by ensuring that a company's profits are accurately reflected through the quality of the audit. The aim of this research is to explore and evaluate the impact of KAP size and auditor specialization on audit quality. This study employs a quantitative methodology using secondary data, with data collection through the documentation method obtained indirectly. The study's population and samples consist of financial statements from manufacturing companies covering the years 2018 to 2022. The analytical approach involves the use of the ANOVA application to perform several analyses, including descriptive statistical tests, classical assumption tests, normality tests, heteroscedasticity tests, and hypothesis tests. The findings of this research indicate that for Hypotheses 1 and 2, which concern the size of the KAP and the specialization of auditors, both resulted in a p-value of 0.336 > 0.05, suggesting that both the size of KAP and auditor specialization influence the quality of the audit. Recommendations for future researchers include using a broader time span for data, incorporating more varied variables, and utilizing data from companies beyond the manufacturing sector Key words: KAP Size, Auditor Specialization, Audit Quality